2005
DOI: 10.1029/2005gl023722
|View full text |Cite
|
Sign up to set email alerts
|

Recent increase in summertime extreme wave heights in the western North Pacific

Abstract: Recent increase in summertime extreme wave heights (H10, June–August average of the highest 10% of significant wave heights at each month) in the western North Pacific is found by applying an empirical orthogonal function analysis to H10 derived from 3rd–generation wave model forced by 6‐hourly sea surface wind fields of NCEP‐NCAR reanalysis over the period 1980–2004. The leading principal component of H10 demonstrates that the highest four years of H10 during 1980–2004 occurred in the last 10 years. It is fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 13 publications
4
18
0
Order By: Relevance
“…More recent studies observe the continuation of this increasing trend into the twenty-first century (Caires et al 2006a;Dodet et al 2010), although there are still uncertainties as to whether, or to what extent, the trend can be ascribed to global warming (Wolf and Woolf 2006;Wang et al 2009). Increasing trends have also been found in other oceans than the Atlantic (Sasaki et al 2005;Gower 2002;Ruggiero et al 2010).…”
Section: Current Trends In the Wave Climatementioning
confidence: 85%
“…More recent studies observe the continuation of this increasing trend into the twenty-first century (Caires et al 2006a;Dodet et al 2010), although there are still uncertainties as to whether, or to what extent, the trend can be ascribed to global warming (Wolf and Woolf 2006;Wang et al 2009). Increasing trends have also been found in other oceans than the Atlantic (Sasaki et al 2005;Gower 2002;Ruggiero et al 2010).…”
Section: Current Trends In the Wave Climatementioning
confidence: 85%
“…Emanuel (2005) showed that, since the mid-1970s, tropical cyclones have become increasingly destructive because of longer storm duration and greater intensity. Sasaki et al (2005) and Yong et al (2008) indicated that summertime extreme wave heights have increased in the western North Pacific during recent years resulting from intense tropical cyclones. Furthermore, extreme hurricane-generated waves in the western North Atlantic have also increased (Komar and Allan 2008;Bromirski and Kossin 2008), and Moore et al (2013) concluded that coastline changes to the U.S. East Coast were attributed to changes in hurricane-generated waves.…”
Section: Introductionmentioning
confidence: 98%
“…Their study estimated that the source of enhancement is about 2400 km south of Japan, coinciding with the geographical position of the cyclonic wind anomaly detected in our present study. Later, Sasaki et al [2005b] and Sasaki and Hibiya [2007] determined that the increase of summertime extreme wave heights was closely related to the increased duration of intense tropical cyclones. Moreover, Stowasser et al [2007] found that the average intensity (measured by the peak wind speed) and the number of intense tropical storms over the entire western North Pacific region increase significantly in global warming simulations.…”
Section: Resultsmentioning
confidence: 99%
“…Summertime extreme SWH is defined as the average of the highest 10% of the 3 hourly model output SWH for each summer (hereafter H top10 ). For extreme wind, we use a definition based on vector wind fields rather than the scalar winds used by Sasaki et al [2005b]. Since changes in a vector field can illustrate variations in wind direction, this approach is useful in the analysis of the associated physical mechanisms related to atmospheric variations.…”
Section: Wave Hindcast Procedures and Data Sets For Trend Analysismentioning
confidence: 99%
See 1 more Smart Citation